Soil prokaryotic community shows no response to 2 years of simulated nitrogen deposition in an arid ecosystem in northwestern China. (27th December 2020) - Huang, Juying; Xu, Yixin; Yu, Hailong; Zhu, Wanwan; Wang, Pan; Wang, Bin; Na, Xiaofan
Summary: An arid ecosystem might be sensitive to nitrogen (N) deposition, but the associated ecosystem‐specific response of soil microbes is not well studied. To assess the N enrichment effects on plant and prokaryotic community diversity, we performed a two‐year NH4 NO3 treatment in a desert steppe in northwestern China. Results showed that N addition increased plant aboveground biomass and decreased plant Shannon diversity. A C4 herb ( Salsola collina ) became dominant, and loss of legume species was observed. The concentrations of soil NH4 + ‐N, NO3 − ‐N, microbial biomass N, and the plant aboveground biomass N pool increased in contrast to total N, suggesting that the N input into the arid ecosystem might mainly be assimilated by plants and exit the ecosystem. Remarkably, the α‐diversity and structure of the soil prokaryotic community did not vary even at the highest N addition rate. Structural equation modelling further found that the plant aboveground N pool counteracted the acidification effect of N deposition and maintained soil pH thus partially stabilizing the composition of prokaryotic communities in a desert steppe. These findings suggested that the plants and N loss might contribute to the lack of responsiveness of soil prokaryotic community to N deposition in a desert steppe.